Training and Workshop to Apply Mathematical Literacy in Classroom for Mathematics Teachers in Dharmasraya - Defri Ahmad; Syafriandi Syafriandi; Jazwinarti Jazwinarti (Fakultas MIPA Universitas Negeri Padang, 2019)
Abstract – 4.0 industry revolution era brings people to have multi-skill ability to survive. In order to prepare multi-skill people Indonesian government create school literacy actions, but this program needs some teachers with strong understanding about literacy. In fact, many teacher do not understand to much about literacy. They only think that literacy is about read. To solve this problem, training and workshop about literacy is needed. Teachers have to know about literacy more spesific especialy literacy that related to their subject. A training and workshop has been done to Junior High School Mathematics teachers in Dharmasraya. In this activity, teachers study about basic understanding of literacy, and mathematical literacy. By some example, teacher try to solve, and to create some mathematics problem related to mathematics literacy. By questioneering this activity teachers say that this program is very good in material, instructor, and activity.